Information literacy and final year trainee teachers: perceptions and practices of the research process / Siri Sena Baba Hamid - Baba Hamid, Siri Sena (2016)
The case study discovers with certainty about information literacy competencies in carrying out research process among trainees of the Malaysian Teacher Education Institute within the five northern region campuses. The Institute has a mission through its dynamic teacher training programmes to produce 21st century world-class trained teachers competent in research skills. In doing so, it is highly important to see that these trainees have acquired a comprehensive understanding of information literacy in their research process. Yet, it is a pivotal fact indicated by recent researchers that most future teachers often enter teaching without the necessary information literacy skills and knowledge in research process. An Information Literacy Research Process Model (ILRPM) is developed to explain the trainees’ behaviour of information literacy seeking skills in accessing, evaluating and applying their needed information when conducting their research process. The scope of study is based on full-time final year undergraduate trainee teachers for the Educational Degree Programme in Kedah, Perlis and Penang, who are required to conduct their school based action research final project paper. The population is segregated into science and non-science from various teacher education content-area specializations. The study uses an in-depth triangulation analysis to investigate information literacy competency problems and issues faced by the trainee teachers in doing their research process. This research is designed as a qualitative exploratory, descriptive and explanatory survey method that uses mix instruments consisting of a questionnaires survey on study population; and two face-to-face interviews with document analysis of theses from the fourteen purposive samples. The three research instruments were mapped to the ILRPM that uses the Information Literacy Standards for Teacher Education (ILSTE) indicators by the Educational Behavioural Sciences Section (EBSS). The findings covers 785 study populations, who believed they can access information (32%), evaluate information (33%) and apply ethical usage of information (35%) through their questionnaire choices. Ultimately, the in-depth interviews and document analysis clearly demonstrate the true understanding of IL seeking skills of these trainees in accessing information (50.28%) and evaluating information (43.1%) as compared to their ability in ethical usage of information (6.62%). The findings had indicated that the IL competencies exist among the northern region trainees; nonetheless, the existence is not equally demonstrated within the trainees’ research processes. This research hopes to specify a clear cut cross section of what the Malaysian trainee teachers had to endure concerning information literacy in research process. The findings can present insights to the ministry’s stakeholders on ways to move forward in terms of needs, process and outcomes according to the Malaysian National Information Literacy Agenda (NILA) in fulfilling the Malaysian Higher Education Blueprint 2015-2025.